2016
DOI: 10.1177/0959683616646182
|View full text |Cite
|
Sign up to set email alerts
|

The Las Salinas palaeo-lagoon in the Sechura Desert (Peru): Evolution during the last two millennia

Abstract: International audienceThe Sechura Desert provides a unique example of a vast palaeo-lagoon system on the Peruvian coast that was active during the first millennium AD.Reconstruction of coastal evolution is made possible by the good resolution of the sedimentary records of the Las Salinas Noroeste coastal plain.Evidence from morphostratigraphy and sedimentary facies indicates marked environmental diversity between the 3rd and the 8th centuries AD and a wide variability of sedimentary dynamics: lagoon foreshores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…14 documents identified by examination of the bibliography of the selected works have been added for the review analysis (Table 2), thus, a total of 70 documents were finally reviewed (Tables 3, 4). [20] WoS, Scopus Urpi Kocha Lagoon (Rio Lurin) Etayo-Cadavid et al ( 2013) [108] WoS, Scopus North and south coast of Moche mouth Hanzalova and Pavelka (2013) [109] Scopus Ciudad Perdida de Huayuri (upper Grande Valley) Macthle and Eitel (2013) [110] WoS, Scopus upper Grance Valley and middle Nazca Valley Kalicki et al ( 2014) [111] Scopus Lomas de Lachay (South of middle Huaura Valley) Nesbitt (2016) [112] WoS Caballo Muerto Archaeological Complex (middle Moche Valley) Caramanica and Koons (2016) [113] WoS, Scopus Pampa de Mocan (middle Jequetepeque Valley) Pavelka et al ( 2016) [114] WoS Cantalloc (upper Nazca Valley) Christol et al (2017) [115] WoS, Scopus West coast of La Leche mouth Wang et al (2017) [116] WoS Salar Grande, Chile Kalicki et al (2018) [117] WoS, Scopus Lomas de Lachay (South of middle Huaura Valley) Delle Rose et al (2019) [23] WoS, Scopus Cahuachi (middle Nazca Valley) Caramanica et al (2020) [118] WoS, Scopus Pampa de Mocan (middle Jequetepeque Valley) Kalicki and Kalicki (2020) [119] WoS Lomas de Lachay (South of middle Huaura Valley) Sandweiss et al (2020) [120] WoS, Scopus Review article Uceda et al (2021) [121] WoS, Scopus Review article Sandweiss and Maasch (2022) [122] WoS, Scopus Review article Rubinatto Serrano et al (2022) [123] WoS, Scopus Rio Muerto and 3 other sites (Moquegua Valley)…”
Section: Screening Resultsmentioning
confidence: 99%
“…14 documents identified by examination of the bibliography of the selected works have been added for the review analysis (Table 2), thus, a total of 70 documents were finally reviewed (Tables 3, 4). [20] WoS, Scopus Urpi Kocha Lagoon (Rio Lurin) Etayo-Cadavid et al ( 2013) [108] WoS, Scopus North and south coast of Moche mouth Hanzalova and Pavelka (2013) [109] Scopus Ciudad Perdida de Huayuri (upper Grande Valley) Macthle and Eitel (2013) [110] WoS, Scopus upper Grance Valley and middle Nazca Valley Kalicki et al ( 2014) [111] Scopus Lomas de Lachay (South of middle Huaura Valley) Nesbitt (2016) [112] WoS Caballo Muerto Archaeological Complex (middle Moche Valley) Caramanica and Koons (2016) [113] WoS, Scopus Pampa de Mocan (middle Jequetepeque Valley) Pavelka et al ( 2016) [114] WoS Cantalloc (upper Nazca Valley) Christol et al (2017) [115] WoS, Scopus West coast of La Leche mouth Wang et al (2017) [116] WoS Salar Grande, Chile Kalicki et al (2018) [117] WoS, Scopus Lomas de Lachay (South of middle Huaura Valley) Delle Rose et al (2019) [23] WoS, Scopus Cahuachi (middle Nazca Valley) Caramanica et al (2020) [118] WoS, Scopus Pampa de Mocan (middle Jequetepeque Valley) Kalicki and Kalicki (2020) [119] WoS Lomas de Lachay (South of middle Huaura Valley) Sandweiss et al (2020) [120] WoS, Scopus Review article Uceda et al (2021) [121] WoS, Scopus Review article Sandweiss and Maasch (2022) [122] WoS, Scopus Review article Rubinatto Serrano et al (2022) [123] WoS, Scopus Rio Muerto and 3 other sites (Moquegua Valley)…”
Section: Screening Resultsmentioning
confidence: 99%
“…So, while the possibility that fuel wood resources could have been obtained over longer distances cannot be completely dismissed, it is more probable that they were collected locally. The only palaeo-environmental study carried out in this area indicates proxy data that in the past the local area around the palaeo-lagoon was characterised by tropical vegetation (even a mangrove type vegetation) during the first millennium AD (Christol et al 2016(Christol et al , 2017. Therefore, our hypothesis with regards to fuel wood acquisition cannot be considered directly with local palaeo-vegetation data.…”
Section: Ancient Environmentmentioning
confidence: 90%
“…This finding is in concordance with the existing evidence that environmental conditions around Bayovar-01 were quite different during the Pre-Hispanic occupation. The presence of a large palaeo-lagoon, resulting in increased water availability (Christol et al 2017), would have supported a dry tropical forest, like that found today on the periphery of the Sechura desert (and elsewhere along the Peruvian coast like the 'Bosque de Pomac' in the Lambayeque region), where water is more abundant (La Torre-Cuadros and Linares Palomino 2008). This dry tropical forest, whose main components are Mimosoideae, and P. pallida in particular, could have provided all of the firewood necessary for the different activities carried out in Bayovar-01, particularly for the processing of large quantities of fish.…”
Section: Ancient Environmentmentioning
confidence: 98%
See 2 more Smart Citations